Talbot-Lau devices: a reappraisal - Gómez-Sarabia, Cristina M.; Ojeda-Castañeda, Jorge (Frontiers in Sensors, 2024)
The Talbot effect and the Lau effect have been usefully applied in optical interferometry, and for designing novel X-ray devices, as well as for implementing useful instruments for matter waves. In temporal optics, the above phenomena play a significant role for reconstructing modulated, optical short pulses that travel along a dispersive medium. We note that the Talbot-Lau devices can be spatial frequency tuned if one employs varifocal lenses as a nonmechanical technique. Thus, we identify a pertinent link between the Talbot-Lau sensors and the development of artificial muscle materials, for generating tunable lenses. Our discussion unifies seemly unrelated topics, for providing a global scope on the applications of the Talbot-Lau effect.